2013
DOI: 10.1177/1367877913507473
|View full text |Cite
|
Sign up to set email alerts
|

Transformative mobile game culture: A sociocultural analysis of Korean mobile gaming in the era of smartphones

Abstract: This article analyzes how mobile gaming has taken shape within the context of Korea's particular online gaming culture. It explores some of the sociocultural factors contributing to the growth of mobile gaming on smartphone platforms in Korea. It discusses how the emergence of smartphone usage has further shaped the development of Korea's mobile games, compared with what one might find in other use cultures and national contexts. It explores the manner in which the transfer to, from, and between online gaming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 18 publications
0
12
0
1
Order By: Relevance
“…Most extant studies are based on only one type of client terminal, such as PCs [19], [26], [29], mobile phones [41], [42], [43] or tablet PCs [52]. However, it is worth exploring whether the conclusions of previous research can be extended to different research backgrounds.…”
Section: Influence Of Devices: Pc and Mobile Phonementioning
confidence: 99%
“…Most extant studies are based on only one type of client terminal, such as PCs [19], [26], [29], mobile phones [41], [42], [43] or tablet PCs [52]. However, it is worth exploring whether the conclusions of previous research can be extended to different research backgrounds.…”
Section: Influence Of Devices: Pc and Mobile Phonementioning
confidence: 99%
“…From a psychosociocultural perspective, few studies have assessed smartphone gaming factors and those that have were conducted in Asia. These include a study in India assessing internal factors ( Banerjee & Das, 2015 ), two in South Korea assessing external factors ( Jang & Ryu, 2016 ; Jin, Chee, & Kim, 2015 ), and one in China assessing external factors ( Liu & Li, 2011 ). The Indian study found several motivations for using mobile games, including convenience, fun, escapism, easy use, visual appeal, and perceived influence of being a positive tool (e.g., being able to stay alone to enjoy gaming or socializing).…”
Section: Introductionmentioning
confidence: 99%
“…The Indian study found several motivations for using mobile games, including convenience, fun, escapism, easy use, visual appeal, and perceived influence of being a positive tool (e.g., being able to stay alone to enjoy gaming or socializing). One of the South Korean studies ( Jin et al., 2015 ), focusing on a sociocultural analysis discussing how the emergence of smartphone use had shaped the development of mobile games, indicated the factors that contributed to increases in smartphone gaming (e.g., a community-based social environment based on technology use). Jang and Ryu ( 2016 ) took a developmental approach examining the relationship between parenting and adolescents’ problematic mobile game use, and suggested overexpectation regarding their children’s potential positively related to problematic mobile game use.…”
Section: Introductionmentioning
confidence: 99%
“…where online yet sedentary gaming practices are increasingly being transformed to mobile and casual ones among urban youth (Jin et al, 2013). …”
Section: Introductionmentioning
confidence: 99%